Service Dimensions and Customer Satisfaction in the Pathao Service Market in Kathmandu Valley - Pathak, Resham Raj; Panthi, Top Lal; Udas, Esmika; Rai, Dev Raj (International Research Journal of MMC, 2026)
Customers play a conclusive role in the survival, growth and success of the service provider. The ability of a service provider to attract and retain their customers has been becoming more crucial factors in the long run. This study assesses major four dimensions influencing customer satisfaction of Pathao services within the Kathmandu Valley, focusing on dimensions of service quality such as acceptability, availability, safety and security and sustainability. Using quantitative and explanatory research design to fulfill the objective of this study; primary data were collected from 390 Patho service users as respondents using structured questionnaires at the February 2026. Correlation analysis reveal that all service dimensions were positively correlated with customer satisfaction. Among these used variables, sustainability emerged as the strongest predictor, followed by safety and security as well as acceptability, while variable called availability with the p value of 0.464 showed no significant impact in regression analysis of this study. The results of this study indicate that customers highly valued environmentally responsible, reliable and secure services. The study concludes that the enhancing key service quality dimensions leads to improved customer satisfaction among the used variables. The findings of this study also provide useful insights for managers, policymakers and researchers to improve service quality within the Pathao users, promote sustainable urban mobility and guide future research in ride-hailing services throughout the world.